Transformation of Task Conflict Into Relational Conflict and Burnout: Enhancing Effect of Leader’s Discriminatory Effect - Hwang, Jaesang; Shin, Kanghyun (Psychological Reports, 2024)
Organizational conflict was proposed by dividing it into task conflict and relationship conflict. However, conflict is dynamic and therefor, the conflict transformation is recognized as an important topic in organizational conflict. In particular, task conflict can be easily transformed into relationship conflict due to emotional expression and misattribution in the process of conflict. In addition, task conflict can negatively affect employees’ attitudes if it is transformed into relationship conflict even though task conflict can function properly. This transformation of conflict can become more active under certain conditions, and leaders play an important role in this transformation because leaders have an important influence on conflict management. Therefore, this study examined the effect of the transition from task conflict to relationship conflict on burnout and the moderating effect of leaders in the relationship between task and relationship conflict. To this end, surveying 721 employees in 15 departments, and multilevel mediation and moderation analysis were performed. As a result of analysis, employees’ burnout increased when task conflict transformed into relationship conflict. In addition, greater the LMX differentiation of leader, greater the effect of task conflict on relationship conflict. Finally, theoretical and practical implications were discussed for leadership and conflict management.
Keywords: Adult; Burnout, Professional; Conflict, Psychological; Female; Humans; Interpersonal Relations; Leadership; Male; Middle Aged; Organizational Culture; burnout; conflict; leader-member exchange; multi-level